Exploring Science Communication Effectiveness in the U.S. Federal Government Research Process: A Case Study with the U.S. Livestock Producers’ Antimicrobial Use Research - Katie Abrams; Chelsea Bonser; Amber McCord (Journal of Applied Communications, 2020)
Several U.S. federal government agencies collect and disseminate scientific data on a national scale to provide insights for agricultural trade, research, consumer health, and policy. Occasionally, such data have potential to provide insights to advance conversations and actions around critical and controversial issues in the broad agricultural system. Such government studies provide evidence for others to discuss, further interpret, and act upon, but to do so, they must be communicated well. When the research intersects with contentious socio-political issues, successful communication not only depends on tactics, but as this study illuminates, it also depends on relationship quality between research producers, study participants, and end-users. USDA’s Animal and Plant Health Inspection Service (APHIS) conducted first-of-its kind national studies on cattle and swine producers’ use of antimicrobials. The use of antimicrobials in animal agriculture is considered a critical and controversial issue pertaining to antimicrobial resistance. In recognition of the anticipated wide-ranging interests in these studies, APHIS sought to understand stakeholders’ perceptions and experiences of the federal government research process and products with aim of improving their science communication and relations. This study reports on findings from in-depth interviews with 14 stakeholders involved in the antimicrobial use studies to make recommendations for improving communication and relations between the agency and its stakeholders. From this research, we draw implications that are transferrable to numerous types of government science communication efforts within agricultural sectors.
Keywords: science communication; antimicrobial use; animal health; relationship quality; knowledge transfer and exchange